Exercise under hypoxia on glucose tolerance in type 2 diabetes mellitus risk individuals: A systematic review and meta-analysis - Hafizah Sururul Nur Rakhmawati; Citrawati Dyah Kencono Wungu; Bambang Purwanto; Andre Andarianto (Tzu Chi Medical Journal)
Objectives: To analyze the impact of exercise under hypoxic exposure versus normoxic exposure on blood glucose level, insulin level, and insulin sensitivity in people at risk of Type 2 diabetes mellitus (T2DM). Materials and Methods: We systematically performed electronic searching on PubMed, Web of Science, ProQuest, and Scopus. Primary studies that met the inclusion criteria were analyzed using Revman 5.4.1. Results: Nine randomized controlled trials were included in this meta-analysis. We found that physical exercise under hypoxic exposure had no significant effect on improving blood glucose levels, insulin levels, and insulin sensitivity in the elderly and sedentary people compared to normoxic condition. However, physical exercise during hypoxic exposure had a significant effect on lowering blood glucose levels in overweight/obese individuals (pooled Standardized Mean Difference = 0.29; 95% confidence interval = 0.01–0.57; P = 0.04). Conclusions: Exercising under hypoxic exposure can be an alternative strategy for reducing blood glucose levels in overweight/obese people. Nevertheless, in other populations at risk of T2DM, exercising in hypoxic conditions gives similar results to normoxic conditions.